Analysis of the Influence of Spiritual and Emotional Dimensions on Customer Loyalty Through Satisfaction as an Intervening Factor at BSI KCP Sinjai - Hasanuddin Atong; Mujahidin; Muh Rasbi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of spiritual dimension, emotional dimension, and service quality on customer loyalty with satisfaction as an intervening variable at Bank Syariah Indonesia (BSI) KCP Sinjai. This research employed a quantitative approach using Structural Equation Modeling–Partial Least Square (SEM-PLS). A total of 100 respondents were selected through purposive sampling. The research instrument was tested for validity and reliability through the outer model, while hypothesis testing was conducted using the inner model. The findings indicate that all independent variables have a positive and significant effect on customer satisfaction and loyalty. Furthermore, satisfaction significantly mediates the relationship between spiritual dimension, emotional dimension, and service quality on customer loyalty. These results highlight that integrating spiritual values, emotional experience, and service quality is a strategic factor in strengthening customer loyalty in Islamic banking.